Development and Evaluation of a Webcam-Based Digital X-Ray Machine Detector with Variable Current and Light Intensity Settings - Narendra, Revindo Prima Sulthon; Mak’ruf, Muhammad Ridha; Triwiyanto, Triwiyanto; Nimir, Yassin (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
X-ray images typically appear as film sheets upon development after undergoing chemical processing. To address these challenges, endeavors were undertaken to create digital X-ray detectors utilizing more cost-effective equipment. This approach involves harnessing variations in current and light intensity to discern disparities in image quality. The noteworthy contribution of this study lies in its ability to exhibit inverted images captured through webcam cameras, subject to prior image processing via the MATLAB application. The utilized measurement ranges encompass 20, 32, and 40 mA, while maintaining a fixed irradiation duration of 1 second and varying the illumination intensity across low, medium, and high levels at a constant 60kV setting. The obtained measurements reveal that the X-Ray Image Capture Device can be juxtaposed with images produced by the Philip brand Digital Radiography, evaluated through the acquired Mean Squared Error (MSE) values. The best picture in this experiment is using system parameter settings with kv of 60kV, 20mA and with low light intensity, and using the PH101 phototransitor. Conversely, the least favorable image records an MSE value of 66.4552p^2 under 60kV 20mA conditions, employing the PH101 Phototransistor sensor and high light intensity. In summary, the outcomes of this study indicate the efficacy of the tool in capturing X-ray images.